Assessment of The Elemental Composition of Ageratum Conyzoides And Its Contribution to Ethno Medicine - Onwudinjo, Uju Felicity; Nnoli , Juliana Nkiru (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aimed at assessing the elemental composition Ageratum conyzoides. The leaves of Ageratum conyzoides (goat weed), has been acknowledged as a non-food source of ethno medicine associated with the treatment of some ailments. The AAS analysis results indicate that the plant contained elements essential for human nutrition. The data were analyzed and the results showed that Ageratum conyzoides leaf extract contained Ca, Mg, Pb, Zn, Al, Cr, Ni, Cu, Co, Cd and Fe were present in the leaves of Ageratum conyzoides. Ageratum conyzoides contains, in addition such acknowledged non-essential and environmentally unfriendly elements as Pb, Co and Cd, which may be a pointer to its non-food use, in combination with its high lipid content. The concentration of minerals in Ageratum conyzoides can be attributed to some of its use such as anti-inflammatory, analgesic, anti-poison, anti-allergic and other therapeutic activities.